Productivity and Profitability of Mesta based Cropping Sequences in North Coastal Zone of Andhra Pradesh - Sadhineni, Malleswari; Joginaidu, G.; Jagannadham, J.; Srilatha, T.; Mitra, S. (International Journal of Bio-resource and Stress Management, 2022)
The field experiments were conducted at Agricultural Research Station, Amadalavalasa, Andhra Pradesh, India during kharif (May and July to October and November) and rabi (Novem and December to variable) of 2018–2020 to evaluate mesta based cropping sequences. Mesta variety AMV 5 was grown during kharif season followed by groundnut (K6), maize (Madhuri), clusterbean (vegetable), greengram (LGG 460), sunnhemp (SH4) and blackgram (LBG 752) during rabi season. Mesta–groundnut/clusterbean crop sequence occupied the field for 256 days followed by mesta–sunnhemp 241 days, mesta–maize (sweet corn) 236 days, mesta–blackgram 231 days mesta–greengram 216 days, while sole mesta occupied the field only for 136 days. Combined analysis of the experimental data revealed that Mesta–Maize (5013 kg ha-1) cropping sequence has produced significantly higher mesta equivalent yield followed by Mesta–Groundnut (4297 kg ha-1) and Mesta–Sunnhemp (2972 kg ha-1). Mesta–Maize has recorded higher system productivity (21.24 kg ha-1 day-1), profitability (Rs. 325 ha-1 day-1, gross returns (Rs. 198302 ha-1), net returns (Rs. 119253 ha-1), BC ratio (2.51) and Relative Economic Efficiency (5.39) followed by Mesta–Groundnut and Mesta–Sunnhemp cropping sequence. Mesta growing farmers of north coastal zone of Andhra Pradesh can realize high productivity and earn profitable returns by adapting Mesta–Maize or Mesta–Groundnut or Mesta–Sunnhemp cropping sequence instead of growing sole mesta based on the available resources and prevailing market demand.